Deprovincializing Philosophy of Religion: From Faith and Reason to the Postcolonial Revaluation of Religious Epistemologies - Sherman, Jacob Holsinger (Journal of the American Academy of Religion, 2018)
While most textbook approaches to the philosophy of religion include a section variously entitled Religious Epistemology, Faith and Reason, or The Rationality of Belief, in this paper I argue that a deprovinicialized, global, and critical approach to the question of faith and reason might now appear more fully under the rubric of the postcolonial revaluation of emic epistemologies. Accordingly, a global-critical philosophy of religion will challenge standard assumptions within contemporary philosophy of religion regarding the normativity of certain approaches to rationality and its justification, on the one hand, and the justification of theism as the central religious question, on the other. I argue that such a deprovinicialized philosophy of religion, while challenging certain secular norms, may embrace a religious and philosophical realism without reenthroning a single religious worldview as either culturally or epistemologically hegemonic.